OBSERVATION OF THE HARD DISRUPTION INSTABILITY IN THE IR-TI (IRAN-TOKAMAK 1) (Journal of Sciences, Islamic Republic of Iran)
In this article, some diagnostic systems and the preliminary results of the IR-T1** (Iran-Tokamak 1) are presented. Different diagnostic methods, including an array of soft X-ray detectors, visible spectrometer, electron cyclotron emission detector and electromagnetic measurement systems have been used and the hard disruptive instability occurring in the IR-T1 plasma during an ohmic heating discharge, under a range of reproducible conditions for 3 q(a) 2, is studied. It is found that the disruption activity occurs when the value of the safety factor at the plasma edge becames less than q(a) 2.7.